Analysis and Testing of Data Transmission of Providers in Indonesia using GSM and CDMA Modem - Fani Rakhman Hakim; Bambang Sugiantoro (IJID (International Journal on Informatics for Development), 2017)
The technology of internet nowadays has become most important aspect and becomes primary need for certain group of peoples who work in some field like education,economy,health,etc. One of the biggest problem which mostly brought by so many people is speed in data transfer. This paper emphasize in directly testing the quality of data transmission from each transmission technology. The equipment used by this paper is ZTE Join Air help, the simcard provided by Telkomsel,XL, and indosat, while CDMA technology used simcard provided by smartfren and esia and modem provided by Smartfren which its series is EC176-2. The parameters used for testing in this paper are throughput, time, jitter dan packet loss. this paper used data gathering method, for each operator and the testing used by this paper is downloading some files from local and non local server, then comparing parameter value between operators.